Polyamine-Mediated Growth Regulation in Microalgae: Integrating Redox Balance and Amino Acids Pathway into Metabolic Engineering - Leandro Luis Lavandosque; Flavia Vischi Winck (SynBio)
Polyamines play a pivotal role in regulating the growth and metabolic adaptation of microalgae, yet their integrative regulatory roles remain underexplored. This review advances a comprehensive perspective of microalgae growth, integrating polyamine dynamics, amino acid metabolism, and redox balance. Polyamines (putrescine, spermidine, and spermine) biology in microalgae, particularly Chlamydomonas reinhardtii, is reviewed, exploring their critical function in modulating cell cycle progression, enzymatic activity, and stress responses through nucleic acid stabilization, protein synthesis regulation, and post-translational modifications. This review explores how the exogenous supplementation of polyamines modifies their intracellular dynamics, affecting growth phases and metabolic transitions, highlighting the complex regulation of internal pools of these molecules. Comparative analyses with Chlorella ohadii and Scenedesmus obliquus indicated species-specific responses to polyamine fluctuations, linking putrescine and spermine levels to important tunable metabolic shifts and fast growth phenotypes in phototrophic conditions. The integration of multi-omic approaches and computational modeling has already provided novel insights into polyamine-mediated growth regulation, highlighting their potential in optimizing microalgae biomass production for biotechnological applications. In addition, genomic-based modeling approaches have revealed target genes and cellular compartments as bottlenecks for the enhancement of microalgae growth, including mitochondria and transporters. System-based analyses have evidenced the overlap of the polyamines biosynthetic pathway with amino acids (especially arginine) metabolism and Nitric Oxide (NO) generation. Further association of the H2O2 production with polyamines metabolism reveals novel insights into microalgae growth, combining the role of the H2O2/NO rate regulation with the appropriate balance of the mitochondria and chloroplast functionality. System-level analysis of cell growth metabolism would, therefore, be beneficial to the understanding of the regulatory networks governing this phenotype, fostering metabolic engineering strategies to enhance growth, stress resilience, and lipid accumulation in microalgae. This review consolidates current knowledge and proposes future research directions to unravel the complex interplay of polyamines in microalgal physiology, opening new paths for the optimization of biomass production and biotechnological applications.